Pengaruh Model Pembelajaran Project-Based Learning Terhadap Hasil Belajar Pecahan Senilai Siswa Kelas IV Sekolah Dasar - Elvina, Meri; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
Mathematics is a subject that contains material concepts of abstract nature. Because of the relative mathematical abstracting is not easy to understand elementary school students in general. Among the many mathematics materials, one of which is an obstacle for students that is a fraction worth. The purpose of this research is to describe the influence of project-based learning model of fractional learning outcomes valued at elementary school grade IV students. This study included experimental research with the research draft of the non-equivalent control group. A sample of research in this study was the student of class IV Elementary School 18 South Freshwater country as many as 23 students as an experimental class and a class IV student elementary School 08 Ulak Karang as many as 22 students as the control class. The test trials were conducted on students of Grade IV Elementary School 07 Ulak Karang. The data collection techniques used in this study include observation, tests, and documentation. The findings showed that on average, a pre-test value in the experimental group was 30.95% and a post-test value of 70.33% or a difference in the study outcomes of the experiment group using the model Project-based learning of 39.38%. Meanwhile, the average pre-test value of the control group is 53.21% and the post-test value is 56.69% or the difference in the learning outcomes in the control group without being given a project-based learning model of 3.48%. Furthermore, the value of Thitung post-test in the experimental group and the control group amounted to 4,218, while a this of 2,016 with a coefficient of P-value of 0.000 < 0.05. It can be concluded that there is the influence of project-based learning model of fractional learning outcomes valued at elementary school grade IV students.